Green technological innovation, green finance, and financial development and their role in green total factor productivity: Empirical insights from China - Jiakui, Chen; Abbas, Jaffar; Najam, Hina; Liu, Jiani; Abbas, Jawad (Journal of cleaner production, 2023)
Considering the environmental deterioration challenges and a sharp decline in the quality and quantity of natural resources, the need for capitalizing on renewable energy sources and environment-friendly practices has increased a lot. The United Nations also has urged firms to shift their reliance on fossil fuels to renewable and eco-friendly practices. Several nations have begun shifting from economic growth to green productivity practices, such as green finance, green innovation, etc., which signifies collaboration between the economy, resources, and ecological development to achieve sustainable development goals (SDGs). This study is based on a comprehensive index of green finance development. Using the nonparametric data envelopment analysis and directional distance function (DEA-DFF) model, it examines the impact of green finance, financial development and green technology innovation (GTI) on green total factor productivity (GTFP) in 28 Chinese provinces from 2011 to 2021. The findings indicate that green finance raises the degree of green productivity significantly. Other elements, such as financial development and technological innovation, contribute significantly to green production. It is also found that establishing green finance legislation can help accelerate the growth of green finance. The empirical findings in this study have policy implications for China's environmental and green finance planning. This study is among the pioneer investigations integrating green finance, financial development, and green technology innovation into a unified research framework. [Display omitted] •Green technological innovation strengthens Chinese green total factor productivity.•Financial development is a significant positive predictor of Chinese green total factor productivity.•Green finance makes a significant positive impact on Chinese green total factor productivity.•Green technological innovation, financial development, and green finance help in achieving green economy objectives.